AI-Powered Writing Tools: Does Word-tune Bring Benefits for EFL Learners’ Writing Performance? - Kholili, Achmad; Afandi, Ahmad (Lumbung Pare Cendekia, 2024)
These days, the use of AI-powered writing tools has been increasingly exploited by some practitioners. These AI tools have brought benefits to learners, especially EFL learners. This facilitates, for example, them with translating, editing and revising stages. However, a technology that understands writers ideas and suggests opinions for rewriting them using different tones and lengths is scarcely used. Thus, the current study attempts to fill this gap. Using a poststructuralist lens, this study attempts to investigate the use of Word-tune as an AI-writing tool by EFL learners. Two EFL learners were recruited to investigate their perception of using Word-tune for writing and invited to join the semi-structured interviews to uncover the benefits of the tool. The results indicate that Word-tune has facilitated them a lot, especially when they need to construct different sentences but still in the original meaning. It also facilitates them with avoiding plagiarism and translation features, making them more easily to understand and improve their writing performance. The suggestions for future studies were offered at the end of this paper.